Arterial Stiffness Assessed by Cardio-Ankle Vascular Index in Patients With Abdominal Aortic Aneurysm and Its Alterations After Treatment. (November 2021) - Mylonas, Spyridon N.; Moulakakis, Konstantinos G.; Kadoglou, Nikolaos; Antonopoulos, Constantinos; Kotsis, Thomas E.; Kakisis, John; Katsenis, Konstantinos; Liapis, Christos
Purpose: The aim of the present study was to investigate a potential difference on the arterial stiffness among aneurysm patients and non-aneurysm controls, as well as to explore potential changes between patients treated either with endovascular or open repair. Materials and Methods: A 110 patients with an infrarenal AAA were prospectively enrolled in this study. Fifty-six patients received an EVAR, whereas 54 patients received an open surgical repair. Moreover, 103 gender and age-matched subjects without AAA served as controls. The cardio-ankle vascular index (CAVI) was applied for measurement of the arterial stiffness. Results: CAVI values were statistically higher in the AAA patients when compared with control subjects. Although at 48 hours postoperatively the CAVI values were increased in both groups when compared to baseline values, the difference in CAVI had a tendency to be higher in the open group compared to the endovascular group. At 6 months of follow up the CAVI values returned to the baseline for the patients of the open repair group. However, in the endovascular group CAVI values remained higher when compared with the baseline values. Conclusion: Patients with AAAs demonstrated a higher value of CAVI compared to healthy controls. A significant increase of arterial stiffness in both groups during the immediate postoperative period was documented. The increase in arterial stiffness remained significant at 6 months in EVAR patients. Further studies are needed to elucidate the impact of a decreased aortic compliance after stentgraft implantation on the cardiac function of patients with AAA.